Effect of essential oil Origanum vulgare L. (oregano) on external otitis by Malassezia spp. in dogs (Canis lupus familiaris) - Rojas, Zaida C. (2015)
The present study aimed to determine the effect of the essential oil of oregano (Origanum vulgare L.) on the external otitis in dogs by Malassezia spp. Were used 38 animals, 22 had bilateral otitis and 16 unilateral (60 ears). Were collected the ear discharge of both ears using sterile swabs and samples were evaluated by performing yeast count per field, after had been subjected to Wright staining. Were made stable dilutions of essential oil of oregano in mineral oil at 1, 2 and 5%. The evaluation of the antifungal effect in vivo was determined by comparing the three dilutions with clotrimazole 1%, used as positive control, and with pure mineral oil in placebo group. The effectiveness of the effect of the dilutions was compared by counting yeasts visual field to the 3rd and 8th day of treatment. Got Better effect to the 8th day with the essential oil of oregano (AEO) 5% with 75% of ears recovered compared to clotrimazole group (50%), concluding that dilution of AEO 5% had a best fungicidal effect on otitis externa in dogs by Malassezia spp.